Implementasi Bauran Pemasaran Syariah terhadap Keputusan Pembelian Kopi Lanang di PT Rolas Nusantara Mandiri - Desy Bariyyatul Qibtiyah; Ulfatul Munawaroh (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the implementation of sharia marketing mix on purchasing decisions for Lanang Coffee products at PT Rolas Nusantara Mandiri . This research uses a qualitative approach by using a descriptive type of research that aims to describe or explain certain situations, events, or phenomena. Data were collected through in-depth interviews, observation, and documentation. The results showed that the sharia marketing mix which includes aspects of product, price, place, and promotion has been implemented according to the principles of halalness, honesty, justice, and social responsibility. The implementation of this sharia marketing mix builds consumer trust, influences positive perceptions, and encourages purchasing decisions. Consumers feel more confident and loyal to products marketed with sharia values. This research contributes to enriching the understanding of the importance of Islamic values in marketing practices, as well as providing practical recommendations for companies in developing sharia-based marketing strategies.